Evidence for Horizontal Gene Transfer of Anaerobic Carbon Monoxide Dehydrogenases - Techtmann, Stephen; Colman, Albert S.; Lebedinsky, Alexander V.; Sokolova, Tatyana G.; Robb, Frank T. (Frontiers in Microbiology, 2012)
Carbon monoxide (CO) is commonly known as a toxic gas, yet it is used by both aerobic and anaerobic bacteria and many archaea. In this study, we determined the prevalence of anaerobic carbon monoxide dehydrogenases (anaerobic CODHs, or [Ni,Fe]-CODHs) in currently available genomic sequence databases. More than 6% (185 genomes out of 2887 bacterial and archaeal genome sequences in the IMG database) possess at least one gene encoding [Ni,Fe]-CODH, the key enzyme for anaerobic CO utilization. The phylogenetic study of this extended protein family revealed nine distinct clades of [Ni,Fe]-CODHs. These clades consisted of [Ni,Fe]-CODHs that, while apparently monophyletic within the clades, were encoded by microorganisms of disparate phylogeny, based on 16S rRNA sequences, and widely ranging physiology. Following this discovery, it was therefore of interest to examine the extent and possible routes of horizontal gene transfer (HGT) affecting [Ni,Fe]-CODH genes and gene clusters that include [Ni,Fe]-CODHs. The genome sequence of the extreme thermophile Thermosinus carboxydivorans was used as a case study for HGT. The [Ni,Fe]-CODH operon of T. carboxydivorans differs from its whole genome in its G+C content by 8.2 mol%. Here, we apply statistical methods to establish acquisition by T. carboxydivorans of the gene cluster including [Ni,Fe]-CODH via HGT. Analysis of tetranucleotide frequency and codon usage with application of the Kullback-Leibler divergence metric showed that the [Ni,Fe]-CODH-1 operon of T. carboxidyvorans is quite dissimilar to the whole genome. Using the same metrics, the T. carboxydivorans [Ni,Fe]-CODH-1 operon is highly similar to the genome of the phylogenetically distant anaerobic carboxydotroph Carboxydothermus hydrogenoformans. These results allow to assume recent HTG of the gene cluster from a relative of C. hydrogenoformans to T. carboxydivorans or a more ancient transfer from a C. hydrogenoformans ancestor to a T. carboxydivorans ancestor.